1998
DOI: 10.1089/end.1998.12.199
|View full text |Cite
|
Sign up to set email alerts
|

Initial Studies of Holmium:YAG Laser Creation of Spinal Defects in Fetal Rabbits: Model for Urologic Effects of Myelomeningocele

Abstract: Myelomeningocele (MMC) is characterized by paraplegia and incontinence, often necessitating surgery. Current models of MMC in sheep and primates create a spinal defect long after anomalous neural tube closure ordinarily occurs. An ideal model of MMC would allow creation of the defect at the earliest age in a low-cost species with a short gestation. We present a method utilizing the holmium laser to create spinal defects in rabbits in utero for the study of the pathophysiology and repair of MMC. Pregnant rabbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
9
2
Order By: Relevance
“…The authors proposed the "two-hint hypothesis" for the mechanism of paralysis: a congenital myelodysplasia complicated by an intrauterine spinal cord injury. The same results were found in pigs and other models like the rabbit since then 5,21,22 . In these studies there was no time interval from the creation of the defect to its correction, so the use of a larger animal model, to permit a prolonged period in utero after surgical manipulation was needed, before extrapolation of these findings to humans.…”
Section: Discussionsupporting
confidence: 82%
“…The authors proposed the "two-hint hypothesis" for the mechanism of paralysis: a congenital myelodysplasia complicated by an intrauterine spinal cord injury. The same results were found in pigs and other models like the rabbit since then 5,21,22 . In these studies there was no time interval from the creation of the defect to its correction, so the use of a larger animal model, to permit a prolonged period in utero after surgical manipulation was needed, before extrapolation of these findings to humans.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies on the creation of a myelomeningocele-like defect in the fetal rabbit reported a fetal death rate varying from 40 [12] to 50% [11], while we found 26% in our series. Although the small numbers on all studies do not permit a statistically significant difference to be demonstrated, this modified technique was found to be a valid alternative method to produce the defect, perhaps safer than the previous ones described.…”
Section: Discussioncontrasting
confidence: 55%
“…When comparing the studies, we would also have to take into account the gestational age at fetal operation, since we expect lower ages to be associated with an increased mortality rate [13]. Both studies [11,12] operated fetuses on days 22-23 and we did it on day 23, so in this regard the studies could be compared. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations